DOES DENTAL STUDENTS' ATTENDANCE IN CLASSROOM LECTURES DEPEND ON THE MODE OF ATTENDANCE TRACKING? - Hani Mawardi; Waad Alharbi; Waleed Alamoudi; Osama Felemban; Soulafa Almazrooa; Emad Alhadlag (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
Purpose: The necessity to attend classroom lectures is a disputable topic among dental schools globally. Since there is an ongoing debate on different aspects of this problem in literature, the purpose of this study was to compare students' attitudes toward classroom attendance and investigate if stricter attendance tracking methods could lead to better classroom attendance at two dental schools utilising different modes of tracking students' attendance. Method: This was an observational, cross-sectional survey distributed among dental students enrolled at King Abdul-Aziz University (KAU) and King Saud University (KSU) in Saudi Arabia. The survey included questions on demographics, average travel time, student's attitudes toward classroom lectures and common reasons for absenteeism. Collected data were analysed and summarised as frequencies and percentages and then compared using the Chi-square test for statistical significance.  Findings: The study involved 678 participants from KAU and 475 participants from KSU. In general, there was a significant difference in students' attendance between both schools in which 26.8% of KAU dental students skipped 5 or more lectures/month compared to 11.5% of students at KSU. Among the factors affecting classroom lecture attendance, commuting time was a major one reported by students (44.8% of students at KSU and 51.4% at KAU needed 30-60 min to reach their schools). The availability of lectures through online resources and the necessity to study for exams were additional factors reported by students of both schools. Implications for research and practices: Based on the current data, the school's method to track students' attendance may have a role in the pattern of classroom absenteeism.